The Medicinal Properties of the Lavender Plant - Muxtorov Asliddin Nosirjon ogli; Karimova Sabina Shuxratbek qizi (American Journal of Bioscience and Clinical Integrity, 2025)
Lavender (Lavandula spp.) is one of the most important medicinal and aromatic plants widely used in traditional and modern medicine due to its strong therapeutic properties. Its essential oil contains biologically active compounds such as linalool, linalyl acetate, cineole, camphor, terpenes, and flavonoids, which demonstrate significant calming, antimicrobial, anti-inflammatory, analgesic, antioxidant, and sedative effects. Numerous scientific studies confirm lavender’s effectiveness in reducing stress, anxiety, and emotional tension, as well as improving sleep quality and supporting the nervous system. Lavender is also useful in treating headaches, respiratory discomfort, skin infections, wounds, burns, and inflammatory conditions. In aromatherapy, it is widely applied to promote relaxation, mental clarity, and emotional well-being. In the context of Uzbekistan, interest in lavender has increased in recent years due to the growing demand for natural and herbal medicine. It is cultivated in various regions, used in herbal teas, essential oils, cosmetics, household aroma therapy, and complementary healthcare practices. Uzbek researchers and medical institutions also recognize lavender’s potential in public health improvement and stress management. Overall, lavender represents an important medicinal resource with strong pharmacological value, cultural relevance, and economic potential. Continued scientific research, responsible application, and effective cultivation can enhance its role in healthcare and natural medicine development in Uzbekistan.